Impact of virtual modality on university education during the COVID-19 pandemic: A public affairs study in Chiclayo, Peru - Salazar, Lorena Liseth Cubas; Lozada, Ricardo Augusto Zapata; Mejía, Percy Junior Castro (Edelweiss Applied Science and Technology, 2025)
University education was greatly impacted worldwide from the onset of COVID-19, which posed unprecedented challenges for learning. This led educators to adapt their in-person classes to an online format due to the highly contagious nature of the disease. As a result, the Peruvian government imposed a nationwide lockdown, suspending all forms of student classes. In this context, our project aims to determine the relationship between virtual modality and university education in response to the COVID-19 pandemic. We employed a basic correlational quantitative approach, collecting data from a sample of 114 university students in the city of Chiclayo, Peru, using online questionnaires with a Likert scale, based on two variables. The results show a very strong positive relationship between virtual modality and university education (Rho=0.921, p=0.00), rejecting our null hypothesis and accepting our specific hypothesis 1, which asserts that there is a significant relationship between organization and accessibility among university students. There is also a demonstrative relationship between planning and technology among university students, as indicated in specific hypothesis 2. Additionally, there is an important relationship between knowledge and pedagogy among university students, as suggested by specific hypothesis 3. This empirical evidence defines that virtual modality has a positive impact on university education. It provides easy access to online learning from anywhere without the need to attend physical classrooms. Most students have internet connectivity and suitable technology for their virtual classes, demonstrating high and positive levels of satisfaction with virtual teaching. This is due to good organization and planning in adapting traditional classes to the virtual modality, which has emerged as a new way to enhance the learning process.